The Implementation of Online Learning in Teaching Reading in an Indonesian Higher Education - Nur Sakinah; Kisman Salija; Muh. Basri Jafar (Har Press Indonesia, 2021)
This study aims to determine how the implement of online learning in teaching reading, lecturers' perspectives on online learning, and the impact of online learning on students' reading achievement. Researchers use observation and interviews as qualitative research instrument case studies. The participants in this research were two lecturers in reading courses at IAIN Bone. The results of this study indicate that two lecturers use two different applications in implementing online learning, namely Google Meet and WhatsApp. In its implementation, it was found that students who use google meet media are more active in class than WhatsApp which spends a lot of time waiting for student responses. The found of the impact of online learning on student achievement is that classes that use google meet as an online learning medium show more improvement than WhatsApp. From the results obtained prove that in the implementation of online learning the media used will affect the improvement of student achievement.